Wafter design for totally enclosed electric machines. (25th January 2018) - Satrústegui, Marco; Artetxe, Gurutz; Elosegui, Ibon; Martinez-Iturralde, Miguel; Ramos, Juan C.
Graphical abstract: Highlights: Design criteria of wafters for totally enclosed electric machines. An experimentally validated CFD model for the modelling of electrical machines. Statistical models to predict the convective heat transfer in the end windings. The influence of wafters in the working temperatures of a particular machine. Abstract: A computational fluid dynamics (CFD) model representing the effect of wafters in a totally enclosed electric machine is presented, introducing the most relevant theoretical assumptions and simplifications. The validation of the model is conducted through experimental measurements. From the CFD simulation data, a second-order response surface is developed using statistical tools, from which the wafters' influence on the convective heat transfer from the stator end windings is predicted. Wafter design criteria are obtained from the response surface information. Finally, a specific case is analysed, showing through CFD simulations that temperatures in the machine are reduced by including wafters in the design.